TRENDS IN MORBIDITY AND MORTALITY OF COLORECTAL CANCER IN MEN AND WOMEN OF CENTRAL SERBIA DURING THE PERIOD 1999-2020 - Nikolic, Aleksandra; Mitrasinovic, Petar; Micanovic, Danilo; Grujicic, Sandra (HEALTH CARE, 2023)
Introduction/Aim: Colorectal cancer is the third leading cancer in terms of morbidity in the world, right after breast and lung cancer, and the second leading malignant tumor according to the number of deaths, after lung cancer. This descriptive study aimed to analyze the trends in incidence and mortality from colorectal cancer in men and women in Central Serbia from 1999 to 2020. Methods: Data on patients and deaths from colorectal cancer (codes C18-C20, according to the International Classification of Diseases), as well as on the number of inhabitants, by sex and age, for the period from 1999 to 2020, were taken from cancer registries in Central Serbia and at the request of the Institute for Public Health of Serbia "Dr. Milan Jovanović Batut". Crude, age-specific and standardized incidence and mortality rates for colorectal cancer were calculated. In order to analyze trends in incidence and mortality rates, joinpoint regression analysis was used. Results: In the period from 1999 to 2020 in Central Serbia, an average of 1696 men and 1112 women were diagnosed with colorectal cancer, and 990 men and 676 women died. In the mentioned period, the average standardized incidence rate (per 100,000) was 34.4 for men and 19.5 for women, and the average standardized mortality rate (per 100,000) was 18.4 for men and 10.1 for women. Average agespecific incidence and mortality rates from colorectal cancer increase with age in both sexes. In the period 1999-2020, the standardized incidence rates of colorectal cancer are increasing significantly by 0.7% per year for women and 1% per year for men. In women, a significant increase in the mortality rate from colorectal cancer of 2.6% per year is observed in the period 1999-2006 year, and then a decline of 1.2% per year for the period 2006-2020. However, in men, a significant increase is observed in the period 1999-2010, followed by a decrease of 1.2% per year, but without statistical significance. Conclusion: It is necessary to work on improving the implementation of organized screening for colorectal cancer, as well as on educating the population about the risk factors for the occurrence of this malignancy and the possibilities for prevention.